PENGEMBANGAN NIAI-NIAI SPIRITUA PROGRAM PESANTREN KILAT PONDOK PESANTREN SIROJU HAROMAIN PONGANGAN INDAH MANYAR GRESIK - Muhaiminah, Muhaiminah (STAI Ihyaul Ulum Gresik, 2025)
In Isam, knowedge and education are highy vaued. Isam does not consider earning ony as a right but more than that, namey, as an obigation. The purpose of organizing a short-term Isamic boarding schoo is to deepen, strengthen and improve the appreciation and practice of Isamic teachings, especiay in terms of Isamic jurisprudence, Monotheism, Isamic History, Akhaqu Karimah and aso Ahussunnah wa Jama'ah. I aso want to appy Isamic teachings in everyday ife to form a soid spiritua mentaity, have a strong personaity, and face various chaenges. This study uses a quaitative approach with a case study type. In data coection techniques, researchers used interview, observation, and documentation methods, using a sampe of Siroju Haromain students at the short-term Isamic boarding schoo, which numbered around 35. The resuts are that this program focuses on instiing spiritua vaues ​​in its students. This program emphasizes three main aspects: Isami, Sharia, and character vaues ​​by introducing nobe moras as a compement to mastery of reigious knowedge and strengthening the image of students as individuas with nobe moras in the eyes of society. The strategy focuses on three aspects: structured and schedued reigious activities, systematic reigious earning, and patient and diigent teachers and mentors.